Β-defensin-3 and β-defensin-4 in synovial fluids from temporomandibular joints with osteoarthrosis. Issue 2 (March 2015) - Leonardi, Rosalia; Crimi, Salvatore; De Ponte, Francesco; Loreto, Carla; Belli, Evaristo; Musumeci, Giuseppe
Abstract Objective This study aimed to analyze β-defensin-3 and β-defensin-4 in human TMJ synovial fluid obtained from patients affected by osteoarthritis (OA), in order to better understand the pathogenic mechanism that underlies this joint damage. Patients and methods A total of 28 joints of 21 patients with diagnosis of OA were involved in the study group. Fourteen joints of 10 volunteers without signs or symptoms of TMJ diseases were used as the control group. The synovial fluid samples were collected from the superior joint cavity by the push-and-pull method. The supernatant was separated and stored in a deep freezer. The expression of β-defensin-3 and β-defensin-4 was evaluated by Western blot analysis. Results Findings obtained through Western blot showed that with respect to the control, both β-defensin-3 and β-defensin-4 were highly expressed (p < 0.01) in OA TMJ synovial fluid; the expression of β-defensin-3 was very strong, while the β-defensin-4 was only strongly expressed. In control TMJ synovial fluid the band density observed was strikingly lower with respect to OA TMJ synovial fluid. Conclusions According to the results obtained, here we hypothesize that β-defensins augment catabolic pathways in articular cartilage, ultimately leading to a timely breakdown of the extracellular matrix, and they participate in the degeneration of the articular cartilage and bone.